Trace Measurements of Ethylene Oxide Using Cavity-enhanced Absorption Spectrometry near 3066 cm−1 - Manish Gupta; Andrew P. Chan; Michael N. Sullivan; Rupal M. Gupta (Aerosol and Air Quality Research)
Abstract Ethylene oxide (EtO) is a key carcinogen that is widely used in the chemical manufacturing and biotechnology industries. Recent work has suggested that permissible exposure limits for EtO be reduced from 1–5 ppm to sub-ppb levels. Such new standards will require new methodologies that are capable of measuring EtO with the requisite precision. In this paper, we demonstrate a new analyzer based on cavity-enhanced absorption spectrometry that utilizes a broad EtO absorption feature near 3066 cm−1. A fit function is developed that includes water, methane, and EtO absorbances and accounts for absorption both inside and outside the cavity. A methane standard is used to determine the cavity gain factor, and the EtO absorbance spectrum is empirically determined. The final system shows excellent linearity from 0–909 ppb EtO (R2 ~0.9999) with a measurement precision of better than ± 1 ppb (1σ, 60 seconds) that improves to ± 0.5 ppb (1σ, 15 minutes). Deliberate ambient EtO releases demonstrate the instrument’s utility in rapidly detecting hazardous conditions. Further work will include improving the measurement precision and directly comparing the system to EPA Method TO-15.